2001
DOI: 10.1116/1.1415512
|View full text |Cite
|
Sign up to set email alerts
|

Development of 157 nm positive resists

Abstract: For adequate transparency we have selected hexafluoroisopropanol as an acid group and an ␣-trifluoromethylacrylic moiety as a repeat unit of our 157 nm resist polymers. The hexafluoroalcohol group is bound to norbornene or styrene. Four platforms are currently available to us: ͑1͒ all-acrylic, ͑2͒ all-alicyclic, ͑3͒ acrylic-alicyclic, and ͑4͒ acrylic-aromatic systems. While the all-alicyclic ͑all-norbornene͒ polymers are synthesized by transition-metal-initiated addition polymerization, all other polymers invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
2

Year Published

2003
2003
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
2
38
0
2
Order By: Relevance
“…15 The contact angle of Poly͑1͒ with TMAH solution is 20°h igher than with Poly͑4͒. In addition to having lower contact angles, solutions of TMAH that contained surfactants gave increased polymer dissolution rates.…”
Section: Dissolution Studiesmentioning
confidence: 97%
“…15 The contact angle of Poly͑1͒ with TMAH solution is 20°h igher than with Poly͑4͒. In addition to having lower contact angles, solutions of TMAH that contained surfactants gave increased polymer dissolution rates.…”
Section: Dissolution Studiesmentioning
confidence: 97%
“…The use of EUV has a marked impact on resist design because the energy of the exposure tools exceeds the ionization potential of the resist materials for mass production. [11][12][13][14] Although the usefulness of halogenation has been proven for conventional resists, halogenation demands particular caution for chemically amplified resists for ionizing radiation. 1 Although some excellent EUV resists have been reported, the requirements for nextgeneration resist materials are so strict that technical solutions are still unknown in many categories such as line width roughness.…”
Section: Introductionmentioning
confidence: 99%
“…1 They found that the protected copolymer could beneficially act as a dissolution inhibitor to the homopolymer to provide enhanced patterning capability. 1 They found that the protected copolymer could beneficially act as a dissolution inhibitor to the homopolymer to provide enhanced patterning capability.…”
Section: Introductionmentioning
confidence: 99%